A review on determining factors for wound healing in diabetic foot ulcers - Melvin Ebin Bondi; Syed Sharizman Syed Abdul Rahim; Richard Avoi; Firdaus Hayati; Azizan Omar; Sahipudin Saupin; Zulkhairul Naim Sidek Ahmad; Syed Sharizman Syed Abdul Rahim; Awang Setia Musleh; Mohammad Saffree Jeffree (2021)
Diabetic Foot Ulcers (DFU) are significant complications of diabetes mellitus. DFU will often heal in a shorter period if factors that inhibit wound healing are identified and managed. This review was to identify determining factors that are associated with wound healing in DFU patients. Glycaemic control, adequate nutrition, presence of infection, the use of modern dressing approach, provide sufficient offloading and avoid unhealthy lifestyle like smoking are the highlighted determining factors discussed in this review and found to have an association towards a timely manner of wound healing in diabetic foot ulcers.